SIMILARITIES BETWEEN COLOR AND WORD COMPOSITIONS - Ojha, Sandeep (International Journal of Research -GRANTHAALAYAH, 2014)
Painting and English Literature depict different aspects of nature and human life. Each color in painting and each word in literature plays an important role in this depiction but a single color or a single word in a work of art is not an absolute entity. The color and the word gain their complete artistic appeal and symbolic significance in a painting or a work of literature when combined and arranged coherently with other colors and words. Great painters and literary writers have dexterity in selection of colors and words of apt meaning and intensity as well as an ability to create the right composition of colors and words to produce an integrated effect.